Ultimate Wolverine. Vol. 1, The Winter Soldier - Condon, Chris (Comics writer) (Ultimate Wolverine, 2025)
"To maintain control of their corner of the Maker's world, three members of his council -- Magik, Colossus and Omega Red -- deploy their most lethal asset: The Winter Soldier! But who is the weapon behind the mask...with the claws? This Ultimate Wolverine will be put to the test by seeing how well he handles the Opposition -- a group fighting for mutant liberation. But when the Winter Soldier leads a strike against two members of the Opposition -- Kitty Pryde and Gambit -- will they recognize their deadly enemy?"--